Role of potassium channels in endothelium-dependent relaxation resistant to nitroarginine in the rat hepatic artery. - Zygmunt, P. M. (1996)
1. In the presence of indomethacin (IM, 10 microM) and N omega-nitro-L- arginine (L-NOARG, 0.3 mM), acetylcholine (ACh) induces an endothelium-dependent smooth muscle hyperpolarization and relaxation in the rat isolated hepatic artery. The potassium (K) channel inhibitors, tetrabutylammonium (TBA, 1 mM) and to a lesser extent 4-aminopyridine (4-AP, 1 mM) inhibited the L-NOARG/IM-resistant relaxation induced by ACh, whereas apamin (0.1-0.3 microM), charybdotoxin (0.1-0.3 microM), iberiotoxin (0.1 microM) and dendrotoxin (0.1 microM) each had no effect. TBA also inhibited the relaxation induced by the receptor-independent endothelial cell activator, A23187. 2. When combined, apamin (0.1 microM) + charybdotoxin (0.1 microM), but not apamin (0.1 microM) + iberiotoxin (0.1 microM) or a triple combination of 4-AP (1 mM) + apamin (0.1 microM) + iberiotoxin (0.1 microM), inhibited the L-NOARG/IM-resistant relaxation induced by ACh. At a concentration of 0.3 microM, apamin + charybdotoxin completely inhibited the relaxation. This toxin combination also abolished the L-NOARG/ IM-resistant relaxation induced by A23187. 3. In the absence of L-NOARG, TBA (1 mM) inhibited the ACh-induced relaxation, whereas charybdotoxin (0.3 microM) + apamin (0.3 microM) had no effect, indicating that the toxin combination did not interfere with the L-arginine/NO pathway. 4. The gap junction inhibitors halothane (2 mM) and 1-heptanol (2 mM), or replacement of NaCl with sodium propionate did not affect the L-NOARG/IM-resistant relaxation induced by ACh. 5. Inhibition of Na+/K(+)-ATPase by ouabain (1 mM) had no effect on the L-NOARG/IM-resistant relaxation induced by ACh. Exposure to a K(+)-free Krebs solution, however, reduced the maximal relaxation by 13% without affecting the sensitivity to ACh. 6. The results suggest that the L-NOARG/IM-resistant relaxation induced by ACh in the rat hepatic artery is mediated by activation of K-channels sensitive to TBA and a combination of apamin + charybdotoxin. Chloride channels, Na+/K(+)-ATPase and gap junctions are probably not involved in the response. It is proposed that endothelial cell activation induces secretion of an endothelium-derived hyperpolarizing factor(s) (EDHF), distinct from NO and cyclo-oxygenase products, which activates more than one type of K-channel on the smooth muscle cells. Alternatively, a single type of K-channel, to which both apamin and charybdotoxin must bind for inhibition to occur, may be the target for EDHF.